Humoral and adaptive immune responses to the SARS-CoV-2 vaccine. (September 2022) - Rizzo, Roberta; Bortolotti, Daria; Morandi, Luca; Rizzo, Sabrina; Schiuma, Giovanna; Beltrami, Silvia; Papi, Alberto; Contoli, Marco
Highlights: SARS-CoV-2 vaccines ameliorate infection and adverse outcomes. The booster dose induces increased humoral immune responses. The booster dose induces an increased adaptative immune response. The booster dose leads to early activation of the memory CD8+ T subset. Abstract: Vaccines against SARS-CoV-2 ameliorate infection and adverse outcomes from SARS-CoV-2. Elicitation of high affinity and durable protective antibody responses is a hallmark of a successful humoral immune response to vaccination. To assess the relevance of serum levels of SARS-CoV-2 specific antibodies and to further characterize the immune response to SARS-CoV-2 vaccines, we report i) the levels of spike-binding and neutralizing antibodies to SARS-COV-2 in the sera of 30 healthy volunteers at nine months after the second vaccination dose of mRNA vaccine and one month after the booster dose; ii) the levels of IFN-γ production by blood T cells exposed to SARS-CoV-2 spike antigen (Wuhan, Alpha B.1.1.7, Delta B.1.617.2, and Omicron B1.1.529 variants); and iii) the specific phenotype of T cells related with exposure to SARS-CoV-2 spike antigen. We observed that the booster dose induced increased humoral and adaptive immune responses and led to early activation of the memory CD8+ T subset.